Application of liquid extraction for wastewater treatment - Dyachok, Vasyl; Venher, Liubov (Видавництво Львівської політехніки, 2024)
This article presents the results of studies of the structure of the emulsion formed in the wastewater of edible oil production. The process of refining edible oils produces stable emulsions that are released into wastewater and pose a threat to the hydrosphere. The main pollutants in these wastewaters are organic substances, mainly of a fatty nature, which existing wastewater treatment plants are unable to treat to the level of sanitary requirements. This creates a significant environmental problem as it causes pollution of surface waters with organic substances. This paper presents the results of studies of the structure of the emulsion formed in the wastewater of edible oil production. The type of emulsifier was determined, and an effective reactive method of emulsion destruction based on the established composition was substantiated. The proposed method of emulsion destruction ensures high-quality wastewater treatment and does not lead to the formation of additional polutants. To achieve a given degree of purification, traditional diagrams have been constructed to determine the number of transfer units that will correspond to the corresponding value of the MPC of polutants. The proposed method of wastewater treatment of edible oil production enterprises makes it possible to solve the problems of reducing environmental pollution and can be implemented in a wide range of changes in the composition of wastewater.
Keywords: wastewater; emulsion; emulsifier; diffusion